Inquiring Sport and Physical Activity students’ perceptions using metaphors as research tools (Investigar las percepciones de los estudiantes de Deporte y Actividad Física utilizando metáforas como instrumento de investigación) - Martínez Ruiz, María Ángeles; Ávalos Ramos, María Alejandra; Merma Molina, Gladys (Retos, 2017)
The aim of this study is to analyse the metaphorical expressions designed by Science of Sport and Physical Activity university students, as a tool of inquiring two research questions: their perceptions of their physical education teachers, and the meaning physical activity has in students’ personal life. 51 students from the University of Alicante have participated in the study. Qualitative data analysis software AQUAD 6 was used for data processing. The results obtained from the analysis of the metaphors designed by students showed that their view of physical education teachers was very positive. The findings also indicate that sport and physical activity were considered to be essential and a source of emotional and physical health. The conclusions also highlighted that students don’t strengthen the social dimension of physical activity, and that it could be imperative to foster a more collaborative learning.